Estudo morfológico e quantitativo dos hemócitos em larvas de Diatraea saccharalis (Fabricius) (Lepidoptera, Pyralidae) - Bombonato, Maria Terezinha Siqueira [UNESP]; Gregório, Elisa A [UNESP] (Sociedade Brasileira de Zoologia, 1995)
Hemocytes of Diatraea saccharalis larvae aging from 13 to 26 days old were morphological and quantitatively characterized by phase contrast microscopy. Six hemocyte types were described and identified as: prohemocytes (PR), plasmatocytes (PL), granulocytes (GR), oenocytoides (OE). spherulocytes (SP) and verm cells (VE). The total hemocyte counts showed no significant difference in the number of these cells along the normal development of the larvae. However, the relative number of different circulating hemocyte types fluctuated, and it could be expressed as: PL > GR > SP> PR > VE > OE in larvae up to 14 days old; and as: GR > SP > PL > VE > OE > PR in those older than 24 days.
Morphological and quantitative studies of the hemocytes in larvae of Diatraea saccharalis (Fabricius) (Lepidoptera, Pyralidae)
Keywords: Lepidoptera; Pyralidae; Diatraea saccharalis; total hemocyte count; differential hemocyte count; hemolymph